Relapse in leprosy and drug resistance assessment in a tertiary hospital of the state of Espírito Santo, Brazil - Danielle Ferreira Chagas; Lucia Martins Diniz; Elton Almeida Lucas; Milton Ozório de Moraes (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTION: Leprosy recurrence is the reappearance of the disease after treatment with current schemes and discharged for cure and may have variable incubation periods. METHODS: This is a descriptive observational study of leprosy recurrence in Espírito Santo diagnosed between January 2018 and January 2020. RESULTS: One hundred and ninety-two cases were available, of which 30 were diagnosed with leprosy recurrence. CONCLUSIONS: In 25 cases, the incubation period was 5-15 years after the first treatment, favoring bacillary persistence. In the remaining 5 cases, the disease had recurred after 15 years, pointing to reinfection as none of them exhibited drug resistance.